Bio-climatic house a sustainable house for Philippine setting - Carlos-Manuel, Jane Anne (Quezon City College of Architecture, University of the Philippines, Diliman, 2002)
To design a bio-climatic house that will respond to the living environment, ecology of the place, conserve resources and promote economy and attain sustainability. It shall include integration of bio-climatic design with zero-waste technology, and eng resource conservation that will help preserve the natural ecology, lessen adverse effect to the living environment and promote green architecture essential for sustainability.
Thesis (Master of Architecture : Architectural Design)--University of the Philippines, Diliman.
Keywords: Dwellings -- Philippines; Houses, Sustainable